An analysis of upper-convected Maxwell nanofluid flow over a stretching surface: Theoretical and numerical approaches - Baskaran Yamuna; Athimoolam Meena; Lakshmanan Rajendran; Mohammad Izadi (Partial Differential Equations in Applied Mathematics)
The flow of fluids in three dimensions is more important in material science, visual design, data science, physical science, the fabrication of plastics, and biological processes.Subsequently, this article has concentrated on investigating nanofluid over a three-dimensional surface in a magnetic field via a bidirectional, non-linearly stretched surface.A mathematical model of the magnetohydrodynamics upper-convected maxwell nanofluid flow is discussed. A set of nonlinear differential equations with a nonlinear component about heat radiation is the basis for this model. The innovation of this research is to analyze the variations in fluid and thermal parameters, namely velocity, temperature, and concentration. It also involves calculating the Nusselt and Sherwood numbers for an upper convected Maxwell nanofluid on a bidirectional stretching sheet. This analysis is being conducted for the first time using analytical (Rajendran-Joy's method) and numerical calculation (Matlab). The analytical results are verified with numerical methods to determine their efficacy and accuracy. The derived analytical results examine the effects of chemical reactions, magnetic fields, and other relevant parameters on temperature, species concentration, and fluid velocity. The graphs and tables show the impact of different variables on velocity, temperature, and concentration. Additionally, a sensitivity study of these variables to velocity is provided.